Large-scale production of Mansonella perstans infective larvae from engorged Culicoides milnei - Kien, Chi Anizette; Ebai, Rene; Fombad, Fanny Fri; Esofi, Frederick; Ntuh, Anna Ning; Ouam, Emmanuel; Gandjui, Narcisse Victor Tchamatchoua; Chunda, Valerine Chawa; Ekanya, Relindis; Nietcho, Franck Noel; Foyet, Juluis Visnel; Nchang, Lucy Cho; et al. (Frontiers in Tropical Diseases, 2024)
BackgroundMansonella perstans is transmitted by Culicoides species and affects hundred millions of inhabitants in about 33 countries in sub-Saharan Africa. It is known that Mansonellosis due to Mansonella perstans do not result in a clear clinical picture, but down-regulates the immunity of patients predisposing them to other diseases like tuberculosis, HIV and malaria or damping vaccine efficacy. However, research about novel drugs against this filarial nematode is missing because of the lack of parasite material. Previous studies have developed in vitro culture systems using infective stage 3 larvae (L3), but these life stages are difficult to obtain and thus the performance of in vitro cultures is restricted and does not allow large-scale testing of drugs or even infection experiments in animal models. Therefore, we aim to establish a platform for the large-scale production of M. perstans infective larvae from engorged Culicoides milnei.MethodsCulicoides species were caught in Yangom (Yabassi Health District) in the Littoral Region of Cameroon following a blood meal on six microfilariae-positive donors with different microfilaraemic loads over one year. Engorged midges were reared in the insectarium for up to 14 days and L3 were isolated from the different body parts.ResultIn summary, 13,658 engorged Culicoides were collected and reared in the laboratory. We observed an overall predicted survival of 78.5%. Out of the 8,123 survived midges, 7,086 midges belong to C. milnei, from which 2,335 were infected leading to a recovery of 6,310 L3. Moreover, we found the highest survival rates of midges during the early dry season in December with moderate temperatures (23-25°C) and low (2-4mm) or no rainfall. In addition, we observed that midges that fed on donors with high microfilarial loads showed increased mortality.ConclusionWe revealed suitable conditions for the collection and maintenance of engorged Culicoides midges allowing the large-scale production of M. perstans L3. This procedure will provide a platform to produce sufficient parasite material that will facilitate in vitro cultures and the establishment of a murine model of M. perstans, which is important for in-depth investigation of the filarial biology and screening of novel drugs that are effective against this ivermectin-resistant nematode.